KLF4-Induced Connexin40 Expression Contributes to Arterial Endothelial Quiescence - Denis, Jean-François; Diagbouga, Mannekomba R.; Molica, Filippo; Hautefort, Aurélie; Linnerz, Tanja; Watanabe, Masakatsu; Lemeille, Sylvain; Bertrand, Julien Y.; Kwak, Brenda R. (Frontiers in Physiology, 2019)
Shear stress, a blood flow-induced frictional force, is essential in the control of endothelial cell (EC) homeostasis. High laminar shear stress (HLSS), as observed in straight parts of arteries, assures a quiescent non-activated endothelium through the induction of Krüppel-like transcription factors (KLFs). Connexin40 (Cx40)-mediated gap junctional communication is known to contribute to a healthy endothelium by propagating anti-inflammatory signals between ECs, however, the molecular basis of the transcriptional regulation of Cx40 as well as its downstream effectors remain poorly understood. Here, we show that flow-induced KLF4 regulated Cx40 expression in ECs. Chromatin immunoprecipitation in ECs revealed that KLF4 bound to three predicted KLF consensus binding sites in the Cx40 promoter. The downstream effects of Cx40 modulation in ECs exposed to HLSS were elucidated by an unbiased transcriptomics approach. Cell cycle progression was identified as an important downstream target of Cx40 under HLSS. In agreement, an increase in the proportion of proliferating cell nuclear antigen (PCNA)-positive ECs and a decrease in the proportion of ECs in the G0/G1 phase were observed under HLSS after Cx40 silencing. Transfection of communication-incompetent HeLa cells with Cx40 demonstrated that the regulation of proliferation by Cx40 was not limited to ECs. Using a zebrafish model, we finally showed faster intersegmental vessel growth and branching into the dorsal longitudinal anastomotic vessel in embryos knock-out or for the Cx40 orthologues Cx41.8 and Cx45.6. Most significant effects were observed in embryos with a mutant Cx41.8 encoding for a channel with reduced gap junctional function. Our data shows a novel evolutionary-conserved role of flow-driven KLF4-dependent Cx40 expression in endothelial quiescence that may be relevant for the control of atherosclerosis and diseases involving sprouting angiogenesis.